2015
DOI: 10.1007/s40292-015-0091-6
|View full text |Cite
|
Sign up to set email alerts
|

HYT-Hypertension in Turkey: A Cross-Sectional Survey on Blood Pressure Control with Calcium Channel Blockers Alone or Combined with Other Antihypertensive Drugs

Abstract: Taken together these findings provide evidence that dihydropyridine-type CCBs, particularly when combined with ACE-inhibitors or angiotensin II receptors blockers, allow to achieve a blood pressure control better than the one reported in the same geographic area by other treatment strategies based on different combinations of diuretics, beta-blockers, ACE-inhibitors, angiotensin II receptors blockers and calcium channel blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…This study revealed that 50.4% of hypertensive patients on outpatient follow-up controlled their BP over the last 6 months. This finding was higher than those of studies conducted in Turkey (31.7%), 13 Malaysia (48.3%), 14 Tanzania (47.7%), 15 Zimbabwe (32.8%), 17 Kenya (33.4%), 18 Uganda (35.9), 16 and similar study in Addis Ababa, Ethiopia (40.1%). 9 This difference is probably due to a change in the criteria used to classify hypertensive patients as having uncontrolled and controlled BP.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…This study revealed that 50.4% of hypertensive patients on outpatient follow-up controlled their BP over the last 6 months. This finding was higher than those of studies conducted in Turkey (31.7%), 13 Malaysia (48.3%), 14 Tanzania (47.7%), 15 Zimbabwe (32.8%), 17 Kenya (33.4%), 18 Uganda (35.9), 16 and similar study in Addis Ababa, Ethiopia (40.1%). 9 This difference is probably due to a change in the criteria used to classify hypertensive patients as having uncontrolled and controlled BP.…”
Section: Discussioncontrasting
confidence: 58%
“… 5 Many studies in different parts of the world show that uncontrolled BP is a common phenomenon among hypertensive patients on treatment. 8 – 11 Thus, BP was controlled for only less than 50% of the hypertensive patients in Japan, 12 31.7% in Turkey, 13 and 48.3% in Malaysia. 14 Controlling BP is a difficult experience in Africa too; BP control was accomplished for only 47.7% of the hypertensive patients on follow-up in Tanzania, 15 35.9% in Uganda, 16 32.8% in Zimbabwe, 17 33.4% in Kenya, 18 and 40.1% in Addis Ababa, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Many studies in different parts of the world show that uncontrolled BP is a common phenomenon among hypertensive patients on treatment. [15][16][17][18] Thus, BP was controlled for only less than 50% of the hypertensive patients in Japan, 18 31.7% in Turkey, 19 and 48.3% in Malaysia. Controlling BP is a difficult experience in Africa too; BP control was accomplished for only 47.7% of the hypertensive patients on follow-up in Tanzania, 20 35.9% in Uganda, 21 32.8% in Zimbabwe, 22 33.4% in Kenya, 23 and 40.1% in Addis Ababa, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is one of the major chronic diseases threatening human health, and it can cause myocardial infarction, renal failure, stroke and death if not detected early and treated properly; currently, more than 1 billion people worldwide suffer from hypertension . Clinically, the main drugs used for treating hypertension are the following: calcium channel blockers (CCBs), diuretics, antihypertensive drugs with central action, vasodilators, angiotensin‐converting enzyme inhibitors (ACEIs), β‐blockers, and angiotensin receptor blockers (ARBs) . In single drug therapy, CCBs are the most commonly used among these drugs because of their remarkable efficacy, extensive drug combination potential and protection of cardiac cerebral vessels .…”
Section: Introductionmentioning
confidence: 99%